PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. TERMINAL TELUK LAMONG SURABAYA - RANGGA SAPUTRA, WISNU (Jurnal Ilmu Manajemen (JIM), 2018)
PT Terminal Teluk Lamong is a new company established four years ago. The company is engaged in ship service, goods service, dry bulk service, and container terminal service. PT Lamong Bay Terminal is a subsidiary of PT Pelabuhan Indonesia III (Persero). This company is the first port in Indonesia that uses the concept of environmentally friendly. "The First Green Port" is the motto of PT Terminal Teluk Lamong to supportenvironmentally friendly harbor concept. This study aims to determine and explain the influence of organizational culture, work environment, and organizational commitment to employee performance on permanent employees at PT Terminal Teluk Lamong. This research is a type of research that uses quantitative approach with a population of 67 people and sampling technique using saturated sampling with a sample of all members of the population. Data analysis techniques using smartPLS software help. The results of this research show that a positive and significant effect of organizational culture on employee performance. The work environment does not effect on employee performance. Organizational commitment have no effect on employee performance. Keywords: organizational culture, working environment, organizational commitment, employee performance